SISTEM PEMBELAJARAN PEDALANGAN PADA USIA LANJUT DI SANGGAR SENI WREDA LARAS DI DUKUH KALONGAN KECAMATAN TASIKMADU KABUPATEN KARANGANYAR SEBAGAI SARANA PENYEMBUHAN - Sukatno Sukatno (Abdi Seni, 2016)
Wreda Laras Art Studio needs for guidance urgently based on taking care of others as consideration that its elder members have different social status. Its members consist of PWRI member surroundings District of Karanganyar, approximately 40-45 people, between 65-75 years old, femalesor males. Wreda Laras Art Studio joined with tradition art like musicians, singers, narrators, and puppeteers. The aim of this activity is making the tradition culture still alive and developing atalent as singers, musicians, or puppeteers. Learning system at Wreda Laras Art Studio—especially puppetry—runs without trainer, then the practice is based on personal experience of its members when they are be PNS (civil servant) actively. This condition is very apprehensive but proud of. The members of Wreda Laras Art Studio have spirit for learning although in elder year. There are some problems with in this learning system: What about the technique for making learning balance basedon the experience of each member? How to get learning system atically? The main aim of this activity is describe and get a proper technique to make learning among members with various experiences harmoniously and have a proper technique about puppetry. The learning result tha tachieved during learning is balancing the relevant concept of puppetry tradition which adapted tocondition of each member and making mental character building as a recovery effort in daily life.The methods which used in puppetry learning at Wreda Laras Art Studio are theory method (cacakansable) and puppetry practice. The materials that performed are: jejer Astino, bedhol jejer, kedhatonan,imbuk and cangik scenes, paseban jaba scene included budalan and kapalan, budalan kreta. However,all members are expected master material such as dhodhogan and keprakan, kombangan LadrangSekar Lesah, dhodhogan and keprakan in jaranan scene, dhodhogan suwuk gendhing Ketawan and Ladrang, and Sabrangan scene.Key words : Wreda Laras, Elder, puppetry